Can the name Mugil cephalus (Pisces: Mugilidae) be used for the species occurring in the north western Atlantic? - Pacheco-Almanzar, Eloísa; Simons, James; Espinosa-Pérez, Héctor; Chiappa-Carrara, Xavier; Ibáñez, Ana L. (Zootaxa, 2016)
Menezes et al. (2010) show that Mugil cephalus Linnaeus, 1758 is different from Mugil liza Valenciennes 1836, the latter being the mullet found along the Atlantic coast of South America. They also suggest that individuals identified as M. cephalus from the northwest Atlantic could represent a population of M. liza in this region, since they doubt the presence of M. cephalus in waters colder than the ones of the West Indies. In order to clarify the presence of M. cephalus in the northwest Atlantic, this study compares meristic and morphometric measurements of M. cephalus and M. liza from the Gulf of Mexico with those obtained by Menezes et al. (2010) for M. liza from South America and for M. cephalus in the Mediterranean Sea. Results show that there are differences in both morphometric and meristic data between the two species. The morphometric measure that differentiates these species is the distance from the snout to the dorsal fin, which is positioned backwards in M. liza compared with M. cephalus. The body width is consistently greater in M. cephalus than M. liza. The meristic character that discriminates between both species is the number of scales in the longitudinal series that, in M. cephalus, ranges from 38 to 43 while in M. liza between 32 to 39. The information presented in this work confirms the presence of M. cephalus in the Gulf of Mexico and the sympatric presence of M. liza is established, even if its abundance is quite low.